Roundtable Discussion: Making Sense of Current Liposuction Technologies. (9th November 2021) - Cook, Jonathan; Pozner, Jason N; Turer, David M; DiBernardo, Barry E; Bharti, Gaurav; Kortesis, Bill; Duncan, Diane I
Abstract: Suction-assisted lipectomy (or "liposuction") is a fundamental technique for all plastic surgeons, and like many procedures in aesthetic surgery, its applications are continuing to evolve. With the rapid introduction of new technologies, many plastic surgeons are left with questions about how these new devices work, what results to expect, and how to best apply these technologies in their practice. We recognized that there is a need for unbiased recommendations to guide surgeons on how to approach current liposuction devices (as well as their adjuncts) and how to use them effectively for their patients. Using available literature and personal experience, we answer the most common questions that we hear from our plastic surgery colleagues.